The professional experiences and training needs of probation officers in Turkey. (September 2019) - Erdem, Gizem; Tuncer, Ayşe Esra; Safi, Ommay Aiman; Çankaya, Banu; Ergin, Murat; Aydoğan, Ramazan
Summary: The current study uses a series of focus groups and participatory methodology to investigate the work experiences and needs of Turkish probation officers and their directors. All participants were employed at an office of Parole and Probation in Istanbul, Turkey. During the concurrent focus groups, officers ( n  = 57) discussed their daily work experiences and needs (Phase I). A follow-up focus group was conducted ( n  = 25) to discuss potential interpretations of the themes and generate solutions (Phase II), followed by a mini-focus group with the directors ( n  = 5) to explore their experiences with the probation system and officer training (Phase III). Findings: Officers identified needs for training, improvements of the work environment, professional support, and more thorough risk assessment tools. The follow-up focus group revealed that officers were highly motivated to improve their rehabilitative skills but felt constrained in supervising offenders in the punitive justice system. Several solutions generated through focus groups included mentoring programs to support novice officers, training programs to acquire interviewing skills, and team building activities and events to increase morale. Application: The current study bridges the gap between officers and directors in the probation system and generates solutions to the occupational needs of officers. Researchers communicated those needs to the directors, and the study initiated action toward implementing rehabilitative training programs for officers with a particular focus on risk assessment and basic clinical skills. The study has direct implications for the improvement of probation practice and supervision in Turkey.